MENELADANI STRATEGI AHLI HADIS DALAM MENYELEKSI RIWAYAT HOAX (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2018)
This research seeks to uncover the efforts and strategies of the hadith scholars in selecting false hadith that began to spread in the hot politics to be linked to the procedures for dealing with hoax news that also spread in the present era. The writing that uses qualitative research methods and sourced from library data finds that these false hadith can be identified by the weakness of the texts, the dislodging system of the sanad and the like that. Then the efforts of the hadith scholars were seen with the massive book of false hadith. Then, also analyze sharply about who is suspected of having forged a hadith. Not only that, the sources of hadith were strongly encouraged to completely close the gap to false hadith. This can be an example so the handling of hoax news must be serious. Because, the essence of fake hadith and hoax news is the same. That is not having clear and accountable source data.